2000
DOI: 10.1128/.74.10.4601-4611.2000
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Borna Disease Virus from Human Brain Tissue

Abstract: Serological and molecular epidemiological studies indicate that Borna disease virus (BDV) can infect humans and is possibly associated with certain neuropsychiatric disorders. We examined brain tissue collected at autopsy from four schizophrenic patients and two healthy controls for the presence of BDV markers in 12 different brain regions. BDV RNA and antigen was detected in four brain regions of a BDV-seropositive schizophrenic patient (P2) with a very recent (2 years) onset of disease. BDV markers exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…Sauder and de la Torre (23) reported that the levels of BDV in blood do not necessarily reflect viral load in the brain. It is also possible that the patients might have experienced a previous infection with BDV which was cleared by the immune system but which still resulted in CNS damage, since viral antigen could be detected in human autopsy brain tissue (27,28)). The third possibility is that our results may be false negative due to the inappropriate timing of blood sampling during the brief transient viremic phase of BDV.…”
Section: Discussionmentioning
confidence: 99%
“…Sauder and de la Torre (23) reported that the levels of BDV in blood do not necessarily reflect viral load in the brain. It is also possible that the patients might have experienced a previous infection with BDV which was cleared by the immune system but which still resulted in CNS damage, since viral antigen could be detected in human autopsy brain tissue (27,28)). The third possibility is that our results may be false negative due to the inappropriate timing of blood sampling during the brief transient viremic phase of BDV.…”
Section: Discussionmentioning
confidence: 99%
“…Infection with SARS-CoV. In addition to Vero E6, the following cell lines were examined for infection by SARS-CoV: human oligodendroglioma-derived cell line OL [22] which was generated at the Wistar Institute, Philadelphia, USA [23]; rat glioma-derived cell line C6 [24]; human intestine-derived cell line CaCo-2; canine kidney-derived cell line MDCK; rabbit kidney-derived cell line RK13. All these cells were similarly infected with SARS-CoV at a multiplicity of infection (MOI) of 10.…”
Section: Methodsmentioning
confidence: 99%
“…It is based mainly on the fact that human sera frequently contain low levels of antibodies that can recognize BDV antigens and that such antibodies are found more frequently in patients with neurological disorders than in healthy individuals (1,5,67). The detection of viral nucleic acids or even infectious virus in patient specimens has been reported by many groups (7,53). However, it is likely that most if not all of these studies were flawed by contamination of patient samples with either laboratory viruses or PCR amplification products (15).…”
mentioning
confidence: 99%